The influence of transition metal oxides type M+/M++ on the vanadium-tellurite glasses electrical behavior - Di Pratula, Pablo Emmanuel (2015)
In this work, the electrical behavior and structural features of the system xCu2O (1-x) (0.5V2O5·0.5MoO3) 2TeO2 compared to xAg2O (1-x) (0.5V2O5·0.5MoO3) 2TeO2 (which was already studied) are explored. The main goal is to determine whether the electronic configuration of Cu+ and Ag+ ions is the key to understand the interactions of these ions with vanadium ions in the glassy matrix studied and to establish the nature of the particular electrical conductivity response. It is shown that despite the fact that both ions (Cu+ and Ag+) have similar electronic configurations but different sizes they have similar electrical behaviors contrary to what is commonly accepted (i.e. silver modified glasses are completely ionic systems, while copper modified glasses are purely electronic epolaronic-semiconductors). It is expected that both behave as mixed electrical conductors, neither pure polaronic nor pure ionic. It has been found that the minimum observed in the isotherm of conductivity can be explained by the structural features of this glassy matrix and not by a change in its mechanism of conduction.